Interleukin-1β Drives Cellular Senescence of Rat Astrocytes Induced by Oligomerized Amyloid β Peptide and Oxidative Stress - Shang, Dongsheng; Hong, Yin; Xie, Wangwang; Tu, Zhigang; Xu, Jun (Frontiers in Neurology, 2020)
Background: Alzheimer's disease (AD) is the leading cause of dementia. With no reliable treatment that delays or reverses the progress of AD, effective medical drugs, and interventions for AD treatment are in urgent need. Clinical success for patients thus relies on gaining a clearer understanding of AD pathogenesis to feed the development of novel and potent therapy strategies. It is well-established that inflammatory processes are involved in the pathology of AD, and recent studies implicated senescence of glial cells as an important player in the progression of AD. Methods: We did a preliminary screen in rat astrocytes for the five most abundant inflammatory factors in neuroinflammation, namely IL-1β, IL-6, IL-8, TGF-β1, and TNF-α, and found that IL-1β could efficiently induce cellular senescence. After that, SA-β-gal staining, immunofluorescence, ELISA, qRT-PCR, and immunoblotting were used to explore the underlying mechanism through which IL-1β mediates cellular senescence of rat astrocytes. Results: IL-1β-induced cellular senescence of rat astrocytes was accompanied by increased total and phosphorylated tau. Further experiments showed that both oligomerized amyloid β (Aβ) and H2O2 treatment can induce cellular senescence in rat astrocytes and increase the production and secretion of IL-1β from these cells. Subsequent mechanistic study revealed that activation of NLRP3 mediates Aβ and H2O2-induced maturation and secretion of IL-1β. Conclusion: Our results suggest that IL-1β mediates senescence in rat astrocytes induced by several common adverse stimuli in AD, implicating IL-1β and NLRP3 as valuable diagnostic biomarkers and therapeutic targets for AD.